The acoustic characteristics of the "Dives in Misericordia" Church in Rome. Issue 2 (June 2021) - Ciaburro, Giuseppe; Iannace, Gino; Trematerra, Amelia; Lombardi, Ilaria; Abeti, Maurizio
This paper discusses the acoustic characteristics of the "Dives in Misericordia" Church in Rome. The church was designed by architect Richard Meier and opened in 2003. It was made entirely of white concrete and consists of three septa with a double curve shaped like a sail. The nave roof is glass. The volume is approximately 14.000 cubic meters. The highest measuring is approximately 26 m. the width of the nave is 19.5 m, while the maximum width is 29.5 m, while the internal length is 32.0 m, while the total length is 45.6 m. It can seat approximately 240 people. The acoustic measurements were taken by placing a microphone at different points of the nave (the area occupied by the audience), with the sound source being placed on the altar. It was therefore possible to obtain a spatial distribution of the average acoustic characteristics inside the church. At a frequency of 1000 Hz, the average values of the reverberation time is about 10 s. In its current configuration, the church is neither suitable for understanding speech nor listening to music. A 3D virtual model was created and with the help of the building acoustics software it was possible to study the sound field inside the church. The possibility to carry out an appropriate acoustic correction was analyzed, in order to reduce the values of the reverberation time, by pacing on a side wall of the church an adequate number of sound-absorbing polyester panels.